Non‐native plants and wildlife in the Intermountain West - Andrea R. Litt; Dean E. Pearson (Wildlife Society Bulletin)
ABSTRACT Non‐native plant invasions can change communities and ecosystems by altering the structure and composition of native vegetation. Changes in native plant communities caused by non‐native plants can influence native wildlife species in diverse ways, but the outcomes and underlying mechanisms are poorly understood. Here, we review and synthesize current information for the Intermountain West of the United States, to develop a general mechanistic understanding of how invasions by non‐native plants affect wildlife, and we identify important information gaps. In this region, most species of recognized conservation and management concern are non‐native forbs (e.g., leafy spurge [Euphorbia esula], spotted knapweed [Centaurea stoebe]), although non‐native grasses (e.g., cheatgrass [Bromus tectorum], medusahead [Taeniatherum caput‐medusae]) also have greatly altered vegetation communities. These invasions by non‐native plants affect native fauna through both trophic and non‐trophic (habitat) pathways and via both direct and indirect effects. The degree to which these invasions affect wildlife depends largely on the degree to which non‐native plants alter form and function of native vegetation communities. Reciprocally, native animals can influence distribution and abundance of non‐native plants by facilitating or inhibiting invasions through herbivory, seed predation, seed dispersal, soil disturbance, and pollination. Current understanding of interactions between non‐native plants and wildlife is limited because few invasions have been studied in sufficient detail to quantify population‐level effects on wildlife reliably or to identify underlying mechanisms causing the observed effects. Although management of non‐native plants has increased in this region, we understand even less about whether control measures can mitigate the adverse effects of non‐native plants on organisms that occupy higher trophic levels. © 2013 The Wildlife Society.